ANALYSIS OF STUDENT ACCEPTANCE OF THE INSTITUTIONAL REPOSITORY OF THE STATE ISLAMIC UNIVERSITY OF NORTH SUMATERA USING THE TECHNOLOGY ACCEPTANCE MODEL (TAM) APPROACH - Siregar, Nur Azizah; Devianty, Rina (PERSPEKTIF: Journal of Social and Library Science, 2023)
This research examines the acceptance of the North Sumatra State Islamic University Library Repository system by students of the 2017 Stambuk Library Science Study Program. The aim of the research is to measure the level of system acceptance from perceived usefulness (PU), perceived ease (PeoU), attitude towards use (AtU), interest. usage behavior (BltU), actual system usage (ASU). Data was collected using an online survey from 90 respondents, consisting of 3 classes of Library Science Study Program students. A quantitative approach is applied using the Technology Acceptance Model (TAM) to measure the level of acceptance of perceived usefulness, perceived convenience, attitudes towards use, behavioral interest in use and actual use of the system. Based on data analysis, the following results were obtained: perceived usefulness had a significant effect on perceived ease of use, perceived usefulness had a significant effect on attitude towards use, perceived ease of use) perceived usefulness has a significant effect on attitudes towards use, perceived ease of use has a significant effect on behavioral intention to use, behavioral intent to use has a significant effect on actual use of the repository system (actual system use), attitude towards use has no effect on actual use of the UINSU repository system (actual system Use). This research contributes to improving human resources for librarians, system stability in utilizing the repository system.